PENDIDIK PROFESIONAL MENURUT SYEKHAL-USAIMIN - Sopian Sinaga (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The independence of our nation is to educatepeople's lives so that we become a dignified nation, a just,prosperous and prosperous nation. For this reason, thegovernment and the DPR have enacted the NationalEducation System Law. One of the important elements ofeducation are educators or teachers or lecturers. The successof education is much influenced by the competence andpersonality of an educator. Therefore, the professionalism ofan educator is emphasized in an effort to achieve educationalgoals. The existence of a figure, namely Sheikh Usaimin, whohas proven successful in giving birth to many figures andscholars, is very interesting to discuss how he thinks aboutprofessional educators. This research is a qualitative typewith a character study approach with a library researchmethod. the information needed was collected from thebooks of Sheikh al-Usaimin namely the book of Majmu'Fatawa wa Rasail Fadilah ash-Shaykh al-Usaimin, the bookof Syarah Riyad as-Salihin and the book of Tafsir Surah alKahf. Analysis of the information obtained was carried out bythe method of content analysis. The results of the study showhow the principles of an educator and how he behaves andbehaves in educating students. Among the principles andattitudes of a professional educator according to Sheikh isthat educators must be happy in teaching, love their students,can be role models for them and be sincere, diligent andcreative in teaching.